GENDER DIFFERENCES OF DYSLIPIDEMIA IN TYPE 2 DIABETICS - Gilani, Syed Yasir Hussain; Bibi, Saima; Ahmed, Nazir; Shah, Syed Raza Ali (Journal of Ayub Medical College Abbottabad, 2010)
Background: Type II diabetic patients are at an increased risk of coronary artery disease and cerebrovascular disease because of deranged lipid metabolism. Female diabetic patients are predominantly at risk. The objective of this cross-sectional study was to determine effects of gender on dyslipidemia of type II diabetic patients. Methods: This study was carried out at Out-Patients Department, Medical A Unit, Ayub Teaching Hospital Abbottabad from 27th May to 27th November 2009. All type II diabetic patients who were above 40 and gave consent were included in the study. Data was collected through a structured proforma. Pattern of dyslipidemia in type II diabetic patients were estimated by computing all the four types of dyslipidemia like hypertriglyceridemia, low HDL, increased serum total cholesterol and increased serum LDL. Results: There were 150 patients with mean age 65.67±11.29 years. There were 80 (53.33%) male and 70 (46.7%) female patients. Mean BMI was 28.45±3.30 Kg/m2. Mean serum cholesterol level was 3.9±1.31 mmol/L, triglyceride level was 2.98±1.14 mmol/L, LDL level was 3.28±0.85 mmol/L and HDL was 0.95±0.02 mmol/L. Women were more frequent to have low level HDL as compare to men (p<0.05), while no significant difference was found regarding serum cholesterol, serum triglyceride and serum LDL (p>0.05). Conclusion: Female diabetic patients have increased frequency of low level of serum HDL as compared to males. Keywords: diabetes, dyslipidemia, gender